Defining guidance across professions - Gomez, Marie Grace Avelino (2007)
In the advent of RA 9258, the definition of Guidance still remains ambiguous for many people, including its major stakeholders. This study sought for the definition of guidance by various professions. Qualitative in nature, the study is constructivist in approach and it utilized grounded theory. It was recommended that information dissemination on guidance services be made to the professionals who make use of Guidance services, to schools and institutions. Education officials should examine the various curricula that are mentioned by the respondents to know if their pre-service training qualifies them to be guidance counselors.